2006
DOI: 10.2174/156652406776894572
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptors and Corneal Innate Immunity

Abstract: The ocular surface is constantly exposed to a wide array of microorganisms. The ability of the cornea to recognize pathogens as foreign and eliminate them is critical to retain its transparency, hence preservation of sight. In the eye, as in other parts of the body, the early response against invading pathogens is provided by innate immunity. Corneal innate immune system uses a series of pattern recognition receptors to detect the presence of pathogens thus allowing for rapid host defense responses to invading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 131 publications
(154 reference statements)
1
108
0
1
Order By: Relevance
“…TLR2 recognizes a broad spectrum of pathogen associated molecular patterns (PAMPs) including PGN, LTA and lipoproteins derived from Gram-positive bacteria [16]. The interaction of TLRs with its PAMP results in the activation of multiple intracellular signaling events such as NF-κB activation and subsequent production of cytokines such as IL-6, IL-8, and TNF-α [2]. The finding that TLR2 neutralizing antibody failed to attenuate SpA-induced inflammatory response suggests that TLR2 is not involved in SpA-mediated inflammatory response in HCECs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TLR2 recognizes a broad spectrum of pathogen associated molecular patterns (PAMPs) including PGN, LTA and lipoproteins derived from Gram-positive bacteria [16]. The interaction of TLRs with its PAMP results in the activation of multiple intracellular signaling events such as NF-κB activation and subsequent production of cytokines such as IL-6, IL-8, and TNF-α [2]. The finding that TLR2 neutralizing antibody failed to attenuate SpA-induced inflammatory response suggests that TLR2 is not involved in SpA-mediated inflammatory response in HCECs.…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of the corneal ocular surface barrier is crucial for the protection of the eye and hence preservation of sight. Studies from our laboratory and others have shown that corneal epithelium, like other mucosal linings in the body, constitutes the first line of defense and plays a critical role in corneal innate immunity [2]. The ability corneal epithelial cells to respond to pathogens is now known to be dependent largely on Toll-like receptors (TLRs), the recently discovered pattern recognizing type 1 membrane receptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 This is partly due to the tight junctions between superficial cells and also partly due to antibacterial peptides and innate immune signalling. [8][9][10][11][12] In addition, bathing tear fluid contains mucins, secretory immunoglobulin A (sIgA), and surfactant protein D, all antimicrobial factors that can bind microbes and potentially alter their interactions with corneal epithelial cells. [13][14][15] Epithelial cells also express several antimicrobial peptides, including human β-defensin 2 (hBD-2), cathelicidin LL-37, 11,12,16,17 and cytokeratin 6A.…”
Section: Corneal Barriers Against Infectionmentioning
confidence: 99%
“…Corneal epithelial cells are located at the ocular surface, and in addition to providing a physical barrier function, they also mediate the immune response to microbial products through the production of proinflammatory cytokines, chemokines, and antimicrobial peptides (9,10). Furthermore, corneal epithelial cells express several TLRs and can respond in vitro to TLR2, TLR3, and TLR5 agonists (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Our previous studies demonstrated that TLR2, TLR4, and TLR9 are expressed in the cornea and can mediate corneal inflammation through the MyD88 adaptor molecule (19,22).…”
mentioning
confidence: 99%